Experimental investigation of isothermal vapor-liquid equilibrium and estimation of excess thermodynamic properties (h(E)) of CHO2K-H2O from 278.15 to 423.15 K - Takalkar, Gorakshnath D.; Bhosale, Rahul R.; Mali, Nilesh A.; Bhagwat, Sunil S. (Journal of Chemical and Engineering Data, 2019)
In this paper, vapor liquid equilibrium (VLE) of a binary mixture, potassium formate-water (CHO2K-H2O), was measured experimentally using a dynamic moving type VLE setup in the temperature range of 313.15 to 393.15 K. Overall, large vapor pressure data points generated for the mole fraction of CHO2K from 0.023 to 0.461 and the solution temperature up to 423.15 K were used to correlate the local composition-based activity coefficient model (NRTL model). The data obtained via the thermodynamic model fitting shows good agreement with the experimental VLE data with overall average relative deviation of 2.15% and root-mean-square deviation of 0.25%. The obtained results further indicate that the binary mixture exhibits a negative deviation from the Raoult's law, which is an important characteristic of the working fluid used for a heat-activated vapor absorption system (VAS). Therefore, the CHO2K-H2O mixture can be considered as an alternative working pair that will overcome the limitations allied to the crystallization and corrosion of the commercial working fluids mainly lithium bromide-water (LiBr-H2O). The fitted nonrandom two-liquid model was further utilized to determine the excess thermodynamic properties, solution enthalpy, solution entropy, and equilibrium P-T-x (Duhring) plot.